Pasos Adelante: The Effectiveness of a Community-based Chronic Disease Prevention Program - Lisa K. Staten, PhD; Linda L. Scheu, MS, MPH; Dan Bronson, MS; Veronica Peña; JoJean Elenes (Preventing Chronic Disease, 2005)
Background Implementing programs that target primary prevention of chronic diseases is critical for at-risk populations. Pasos Adelante, or Steps Forward, is a curriculum aimed at preventing diabetes, cardiovascular disease, and other chronic diseases in Hispanic populations. Pasos Adelante is adapted from the National Heart, Lung, and Blood Institutes cardiovascular disease prevention curriculum, Su Corazón, Su Vida, and includes sessions on diabetes and community advocacy and incorporates walking clubs. Context The Pasos Adelante curriculum was implemented in two Arizona, United States-Sonora, Mexico border counties. Key issues in these communities are safety, access to recreational facilities, climate, and cultural beliefs. Methods Pasos Adelante is a 12-week program facilitated by community health workers. The program includes interactive sessions on chronic disease prevention, nutrition, and physical activity. Evaluation of the program included precurriculum and postcurriculum questionnaires with self-reported measures of physical activity and dietary patterns. Approximately 250 people participated in the program in Yuma and Santa Cruz counties. Consequences Postprogram evaluation results demonstrate a significant increase in moderate to vigorous walking among participants and shifts in nutritional patterns. Interpretation The Pasos Adelante program demonstrates that an educational curriculum in conjunction with the support of community health workers can motivate people in Arizona/Sonora border communities to adopt healthy lifestyle behaviors.